Social Capital and Local Development Activities: A Rural Development Perspective (Research Nepal Journal of Development Studies, 2018)
This paper examined the status of social capital and local development activities in Thapagaun village of Kirtipur Municipality. The focus has been given to explore role of social capital on local development from the perspective of rural development. More so, under the mix method study design, ethnographic methodology has been applied. In so doing, I selected 28 total households of Thapa community as respondents and also selected four participants from migrated households as participants purposively. The necessary primary data was collected and generated through household survey questionnaire, in depth interview and participant observation whereas secondary information generated from municipality profile, published journal articles and books. More specifically the study revealed with three types of social relationships (i.e. bonding, bridging and linking) that have been improving socio-economic and cultural life of the villagers in the study area. This study found that socio economic, cultural and educational status of the respondents have been playing key role for forming social capital and promoting local development activities though condition of road networking and transportation facilities are still found to be unsatisfactory. However, women are thoughtfully playing socio-economic and cultural role in the community as an outcome of social capitals. Finally, the study realized that reciprocal relationship among villagers and linking relationship with politicians/bureaucrats have been affected local development activities in this community.